Factor Analysis On Customer Satisfaction At Bella Vita Hotel - Gabriela Roselin Wongge (Fakultas Bisnis, 2020)
Tourism industry in Indonesia is growing rapidly every year. This requires Bella Vita Hotel to maintain and develop the company to increase sales, maintain customer loyalty, and attract more customers by increasing customer satisfaction. The researcher uses service quality, price, facility, and customer satisfaction as the reference variables for this study. The purpose of this study is to analyze the factors that influence the level of customer satisfaction at Bella Vita Hotel. The population of this study is 152 people, taken from the average data of customers that stayed at Bella Vita Hotel from May-July 2019. Therefore, the number of samples obtained through the calculation using the Slovin Formula is 61 people. The researcher collected the primary data by distributing questionnaires to 61 customers of Bella Vita Hotel, and the sample is selected using Simple Random Sampling and processed using SPSS 22. Exploratory Factor Analysis is the technique of data analysis used in this study. The result of this study are 7 new variables with each operational item inside, namely: Personal Experience, Benefit, Company Image, Employee Capabilities, Customer Oriented, Feedback, and Price.